CHLAMYDIA INFECTION IN PREGNANT WOMEN: POSSIBILITIES OF FETAL AND NEONATAL ASSESSMENT USING SOME ACUTE-PHASE BLOOD PARAMETERS AND LOGISTIC REGRESSION METHODS - Гребнева, Вероника Сергеевна; Ренге, Людмила Владимировна; Зорина, Вероника Николаевна; Григорьева, Екатерина Юрьевна; Власенко, Анна Егоровна (Mother and Baby in Kuzbass, 2022)
The purpose of the study – assessment of the level of some serum indicators of acute-phase proteins (alpha2-macroglobulin, alpha1-antitrypsin and lactoferrin) as risk factors for congenital infectious diseases (VIZ) of the fetus and newborn from pregnant women with chlamydia infection of various form. Materials and methods. Venous blood was studied in 125 pregnant women at 37-41 weeks gestation with chlamydia infection with various variants of its course. The first group included 83 women with an acute course of chlamidium infection (PCR test+, IdM+, IgG+/-); 44 patients had children with congenital infectious diseases (VIZ), and 39 had healthy children. The second group consisted of 42 pregnant women with the carrier of the pathogen Chlamydia trachomatis (PCR test–, IdM-, IgG+), 22 of them had newborns with VIZ and 20 had healthy children. Serum proteins were determined in the blood serum: alpha2-macroglobulin (a2-MG) and alpha-1-antitrypsin (a1-AT) by quantitative rocket immunoelectrophoresis, as well as the level of lactoferrin (LF) by solid-phase enzyme immunoassay (ELISA). Results. In the blood serum of pregnant women with acute infection and the birth of children with VIZ, an increased concentration of alpha2-MG, LF, a1-AT (a2-MG more than ≥ 2.8 g/l, a1-AT ≥ 3.4 g/l, LF ≥ 4.0 g/l) was found in comparison with the indicators of proteins in pregnant women of the same group who gave birth to healthy children. Pregnant women with the carrier of the pathogen Chlamydia trachomatis, who gave birth to children with a VISA, had an increased concentration of only LF (LF ≥ 4.0 mg/l), compared with those who gave birth to healthy ones. Conclusion. The determination of a2-MG, a1-AT, LF in the blood serum of pregnant women with the presence of Chlamydia trachomatis and the use of the logistic regression method revealed highly reliable predictors of intrauterine infection in the fetus and newborns.